Immune Thrombocytopenia Induced by Immune Checkpoint Inhibitrs in Lung Cancer: Case Report and Literature Review - Xie, Wang; Hu, NaNa; Cao, LeJie (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICIs), including antibodies targeting programmed cell death protein-1 (PD-1) and programmed cell death ligand-1 (PD-L1), are being extensively used on advanced human malignancies therapy. The treat of ICIs have acquired durable tumor inhibition and changed the treatment landscape in lung cancer. Immune-related adverse events including pneumonitis and thyroiditis have been well described, but less frequent events, such as ICIs-induced thrombocytopenia, are now emerging and may sometimes be severe or fatal. Since early detection and prompt intervention are crucial to prevent fatal consequences, it is of outmost importance that medical staff is aware of these potential toxicities and learn to recognize and treat them adequately. This review focuses on the epidemiology, clinical presentation, mechanisms, and clinical management of ICIs-induced thrombocytopenia in patients with lung cancer. We also present a patient with advanced lung adenocarcinoma who received the PD-L1 inhibitor atezolizumab and eventually developed severe thrombocytopenia. The case indirectly suggests that cytokine changes might contribute to immune dysregulation in ICIs-induced thrombocytopenia.